Exposure to Direct Sunlight during the Growing Season Delays Postharvest Softening of ‘Williams’ Pears and Improves Their Response to 1-Methylcyclopropene - Raffo Benegas, Maria Dolores; Sanchez, Enrique Eduardo; Sozzi, Gabriel Oscar (International Society for Horticultural Science (ISHS), 2025)
Trabajo presentado al X International Pear Symposium, Peniche (Portugal), mayo de 2007